Ethics in science : ethical misconduct in scientific research - D'Angelo, John. (London : CRP Press, 2012)
"Providing the tools necessary for a robust debate, this book explains various forms of scientific misconduct and describes real ethical controversies that have occurred in science. The first part of the book includes a description of a variety of ethical violations, why they occur, how they are handled, and what can be done to prevent them along with a discussion of the peer-review process. The second part of the book presents real-life case studies that review the known facts and allows readers to decide for themselves whether an ethical violation has occurred and what should be done"--
Includes bibliographical references and index.
Keywords: Research -- Moral and ethical aspects -- Case studies